Lifestyle Activities That Contribute to The Risk of Stroke in Indonesia: Smoking, Consuming Fatty Foods and Soft Drinks - Janu Purwono; Irwan Budiono; Oktia Woro Kasmini Handayani (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Stroke is the leading cause of death and disability in Indonesia, with a high prevalence reported in the Indonesian Health Survey (IHS) 2023. Smoking, consumption of fatty foods, and intake of soft drinks are major risk factors contributing to the increasing incidence of both ischemic and hemorrhagic stroke. This study aims to analyze the effects of smoking habits, fatty food consump-tion, and soft drink intake on stroke incidence in Indonesia using secondary data from IHS 2023. A quantitative design was applied, with chi-square test analysis performed using SPSS. The study population comprised all individuals recorded in the IHS 2023, which covered 38 provinces in Indonesia. Results showed that the age group 65–74 years had the highest incidence of stroke (35.4%), with a higher prevalence among men (8.8%) compared to women (7.9%). Education level and type of occupation were also associated with stroke prevalence. Statistical analysis demonstrated that smoking (p = 0.013), fatty food consumption (p = 0.003), and soft drink intake (p = 0.002) were significantly associated with stroke incidence. Among these, soft drink con-sumption was the strongest predictor (p = 0.001; OR = 3.717). In conclusion, smoking, fatty food consumption, and soft drink intake significantly affect stroke incidence in Indonesia, with soft drink consumption being the most influential factor.